Admission of the very elderly to the intensive care unit: Family members' perspectives on clinical decision-making from a multicenter cohort study. (April 2015) - Heyland, Daren K; Dodek, Peter; Mehta, Sangeeta; Cook, Deborah; Garland, Allan; Stelfox, Henry T; Bagshaw, Sean M; Kutsogiannis, Demetrios J; Burns, Karen; Muscedere, John; Turgeon, Alexis F; Fowler, Rob; et al.
Background: Little is known about the perspectives and experiences of family members of very elderly patients who are admitted to the intensive care unit. Aim: To describe family members' perspectives about care provided to very elderly critically ill patients. Design: Multicenter, prospective, cohort study. Participants and setting: In total, 535 family members of patients aged 80 years or older admitted to 22 intensive care units for more than 24 h. Results: Family members reported that the "patient be comfortable and suffer as little as possible" was their most important value and "the belief that life should be preserved at all costs" was their least important value considered in making treatment decisions. Most family members (57.9%) preferred that life support be used for their family member, whereas 24.1% preferred comfort measures only, and 14.4% were unsure of their treatment preferences. Only 57.3% reported that a doctor had talked to them about treatment options for the patient. Overall, 29.7% of patients received life-sustaining treatments for more than 7 days and 50.3% of these died in hospital. Families were most satisfied with the skill and competency of nurses and least satisfied with being included and supported in the decision-making process and with their sense of control over the patient's care. Conclusion: There is incongruity between family values and preferences for end-of-life care and actual care received for very elderly patients who are admitted to the intensive care unit. Deficiencies in communication and decision-making may be associated with prolonged use of life-sustaining treatments in very elderly critically ill patients, many of whom ultimately die.